Balloon catheter versus basket catheter for endoscopic bile duct stone extraction: a multicenter randomized trial - Ishiwatari, Hirotoshi; Kawakami, Hiroshi; Hisai, Hiroyuki; Yane, Kei; Onodera, Manabu; Eto, Kazunori; Haba, Shin; Okuda, Toshinori; Ihara, Hideyuki; Kukitsu, Takehiro; Matsumoto, Ryusuke; Kitaoka, Keisuke; Sonoda, Tomoko; Hayashi, Tsuyoshi; for the Hokkaido Interventional EUS/ERCP Study (HONEST) Group (Endoscopy, 2016)
Background and study aims: Endoscopic bile duct stone (BDS) removal is a well-established treatment; however, the preference for basket or balloon catheters for extraction is operator-dependent. We therefore conducted a multicenter prospective randomized trial to compare catheter performance.Patients and methods: We enrolled patients with a BDS diameter ≤ 10 mm and common bile duct diameter ≤ 15 mm. Participants were randomly assigned to groups that were treated with basket or balloon catheters between October 2013 and September 2014. The primary endpoint was the rate of complete clearance of the duct; the secondary endpoints were the rate and time to complete clearance in one endoscopic session.Results: We initially enrolled 172 consecutive patients; 14 were excluded after randomization. The complete clearance rates were 92.3 % (72/78) in the balloon group and 80.0 % (64 /80) in the basket group. The difference in the rates between the two groups was 12.3 percentage points, indicating non-inferiority of the balloon method (non-inferiority limit −10 %; P < 0.001 for non-inferiority). Moreover, the balloon was superior to the basket (P = 0.037). The rate of complete clearance in one endoscopic session was 97.4 % using the balloon and 97.5 % using the basket (P = 1.00). The median times to complete clearance in one endoscopic session were 6.0 minutes (1 – 30) and 7.8 minutes (1 – 37) in the balloon and basket groups, respectively (P = 0.15).Conclusions: For extraction of BDSs ≤ 10 mm, complete endoscopic treatment with a single catheter is more likely when choosing a balloon catheter over a basket catheter.University Hospital Medical Information Network Trials Registry: UMIN000011887.